Pleistocene glacitectonic landforms and sediments around central Magellan Strait, southernmost Chile: evidence for fast outlet glaciers with cold-based margins - Benn, Douglas Iain; Clapperton, CM (2000)
Proglacial and subglacial glacitectonic sediments and landforms around the margins of the Strait of Magellan, southernmost Chile, record the advance and retreat of outlet glaciers of the Patagonian ice cap during the last glacial cycle. The spatial arrangement of glacitectonic landforms in the area is inferred to have resulted from the advance of ice lobes with cold-based margins and wet-based interiors. As the ice advanced. subglacial basins were excavated beneath the glacier margins and the eroded material was pushed up into thrust moraines. probably because frozen-bed conditions formed a thermal dam against the free drainage of subglacial meltwater. These ice-marginal glacitectonic landforms were then overridden and streamlined into drumlins and flutes as thicker, wet-based ice passed over the area. Evidence for permafrost near sea level in Patagonia during the last glaciation suggests that mean annual temperatures were several degrees lower than indicated by recent modelling studies. The results indicate that future modelling experiments should incorporate more realistic basal boundary conditions, particularly the presence of a weak deforming layer at the glacier bed, to improve climatic reconstructions of southern South America. (C) 2000 Elsevier Science Ltd. All rights reserved.